2017
DOI: 10.1021/acs.jpca.7b01961
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Release from Cationic Niobium–Vanadium Oxide Clusters, NbnVmOk+, Revealed by Gas Phase Thermal Desorption Spectrometry and Density Functional Theory Calculations

Abstract: Thermal dissociation of the cationic niobium-vanadium oxide clusters, NbVO (n + m = 2-8), was investigated by gas phase thermal desorption spectrometry. The oxygen-rich NbVO released O and O for odd and even values of n + m, respectively. Substitution of more than one Nb atom in NbO by V drastically lowered the desorption temperature of O for even values of n + m, whereas the substitution of more than two Nb atoms opened a new desorption path involving the release of O for odd values of n + m. The substitution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In the condensed-phase studies for CO 2 utilization, the temperature effect on the product selectivity has been readily explored . In the gas-phase studies, the high-temperature experiments have been rarely reported and the available examples typically explored are the reaction systems of metal oxide clusters. Recently, the reaction of FeC 3 – anion with CH 4 at high temperatures (300–610 K) was reported and the production of C 2 H 2 via C–C coupling was identified . The reaction of CO 2 on liquid Al 100 + species that was preheated in the cluster source was reported by Jarrold and co-workers .…”
Section: Discussionmentioning
confidence: 99%
“…In the condensed-phase studies for CO 2 utilization, the temperature effect on the product selectivity has been readily explored . In the gas-phase studies, the high-temperature experiments have been rarely reported and the available examples typically explored are the reaction systems of metal oxide clusters. Recently, the reaction of FeC 3 – anion with CH 4 at high temperatures (300–610 K) was reported and the production of C 2 H 2 via C–C coupling was identified . The reaction of CO 2 on liquid Al 100 + species that was preheated in the cluster source was reported by Jarrold and co-workers .…”
Section: Discussionmentioning
confidence: 99%
“…In thermal desorption spectrometry experiments, the clusters travel down a 116 mm long extension of the reaction zone formed by a copper tube of larger diameter, which reduces the number of reactive collisions. [76][77][78][79][80][81][82][83][84][85] Crucially, this tube is thermally isolated from the reaction zone and can thus be heated without significantly changing the temperatures of the source and the subsequent reaction zone. In addition, the helium carrier gas cannot escape and forms a thermal link with the heated tube wall, thus ensuring that the reaction products thermalize.…”
Section: Rhodium Cluster Production and Reaction Under Thermalized Co...mentioning
confidence: 99%